Effects of visual exercises training on developing ball velocity and accuracy shooting of penalty corner in field hockey - Ali Badr, M. A. (International Journal of Sports Science and Arts, 2019)
The primary aim of this study was, therefore, to investigate the effect of visual training on visual abilities of field hockey female players. A secondary aim was to examine the effect of visual training on velocity of ball shooting in penalty corner of field hockey female players, and the third aim was to determine the effect of visual training on accuracy of ball shooting in penalty corner of field hockey female players. The researcher has used the expermintal design for one group from the first female Sahrkia Club team. Twelve players were participated in this study and underwent for pre and post tests after the visual exercises training over 8 weeks, which considered 3 training times every week. The results of current study indicate that, the visual skills such as eye coordination, anticipation time and concentration were very important factors when players performed the penalty corner situation in field hockey matches.